The Association Between Changes in Red Cell Distribution Width and Mortality Among Sepsis Patients in the Intensive Care Unit at Hasan Sadikin Hospital, Bandung. - Hendro, Rachmad Try; Pradian, Erwin; indriasari, indriasari (Syifa'Medika, 2026)
Sepsis is a leading cause of mortality, especially in developing countries. Sepsis biomarkers are needed for diagnostic and prognostic purposes to determine therapeutic effectiveness. Currently, available biomarkers are expensive and not all are available, especially in remote areas. Red Cell Distribution Width (RDW) is a laboratory parameter commonly used to diagnose anemia and can describe the variability of red blood cell shape and size. In sepsis, inflammation and oxidative stress occur, resulting in changes in red blood cell age and maturation, which can affect RDW results. This study aims to examine the relationship between trends in RDW results and mortality in sepsis patients. This retrospective, observational, analytical study was conducted on 71 ICU patients at Dr. Hasan Sadikin General Hospital, Bandung, from 2024 to 2025. In this study, patients were divided into two groups: mortality and survival. RDW was assessed on the first and third days in both groups. The results of this study showed that RDW in the mortality group was higher than in the survival group, 80% and 41.9% (p = 0.001). In the mortality group, 85% of patients experienced a statistically significant increase in RDW on the third day compared to the survival group (p=0.0001) with positive moderat correlation (Contingency Coefficient 0.494). This demonstrates a positive moderate relationship between increased RDW and mortality in sepsis patients. Trend of changes in RDW values can be used to assess mortality risk in sepsis patients in the ICU.